Effects of Residential Environment and Lifestyle on Atopic Eczema Among Preschool Children in Shenzhen, China - Liu, Yanlin; Sun, Shujie; Zhang, Duo; Li, Wenchen; Duan, Zhenya; Lu, Shaoyou (Frontiers in Public Health, 2022)
Eczema, one of the most prevalent inflammatory skin diseases among children, is potentially influenced by genetic, environmental and social factors. However, few studies have investigated the effect of residential environment and lifestyle on childhood eczema. Therefore, this study conducted a cross-sectional study based on 2,781 preschool children in Shenzhen, China, during 2015–2016. A logistic regression model was employed to analyze the associations between residential/household environment, lifestyle, dietary habits and doctor-diagnosed eczema in children. The prevalence of eczema among children in Shenzhen was 24.6%. Significant associations (increased odds >50%, P<0.05) were found between childhood eczema and the factors of using composite wood floors (adjusted OR=1.777, 1.911), living in a villa/townhouse (3.102, 2.156), the presence of mold or damp stains in the child’s room (1.807, 2.279), and rarely cleaning the child’s room (1.513, 1.540). In addition, too much time spent watching TV/playing with a computer was significantly associated with an increased risk of eczema, while a moderate intake of vegetables and fruits could decrease the risk of childhood eczema. In addition, ambient air pollution, in the covariates, may also affect childhood eczema. Therefore, avoiding these adverse factors and creating a low risk environment are crucial to prevent childhood eczema.